The Current Energetics of Earth's Interior: A Gravitational Energy Perspective - Morgan, Jason P.; Rüpke, Lars H.; White, William M. (Frontiers in Earth Science, 2016)
The Earth's mantle convects to lose heat (Holmes, 1931); doing so drives plate tectonics (Turcotte and Oxburgh, 1967). Significant gravitational energy is created by the cooling of oceanic lithosphere atop hotter, less dense mantle. When slabs subduct, this gravitational energy is mostly (~86% for whole mantle flow in a PREM-like mantle) transformed into heat by viscous dissipation. Using this perspective, we reassess the energetics of Earth's mantle. We also reconsider the terrestrial abundances of heat producing elements U, Th, and K, and argue they are lower than previously considered and that consequently the heat produced by radioactive decay within the mantle is comparable to the present-day potential gravitational energy release by subducting slabs—both are roughly ~10–12 TW. We reassess possible core heat flow into the base of the mantle, and determine that the core may be still losing a significant amount of heat from its original formation, potentially more than the radioactive heat generation within the mantle. These factors are all likely to be important for Earth's current energetics, and argue that strong plume-driven upwelling is likely to exist within the convecting mantle.